Validity and Reliability of a Questionnaire in Exploring the Protective Factors of Mental Health in Cuban University Students - Fernández-Castillo, Evelyn (2017)
Objective: To analyze the validity and reliability of a questionnaire in exploring the protective factors of mental health in Cuban university students. Method: The sample was composed of 1377 students. A categorical principal components analysis, a two-step cluster analysis and decision trees were used. Results: Results revealed two components. The first dimension included items that have a positive meaning and express a development of these protective factors. This dimension showed a higher coefficient of reliability and was able to explain a higher proportion of the variance in the clusters identified. The second dimension grouped those items that were related to poor development of these protection factors, which could constitute to risk factors. Items associated with resilience, decision making ability, self- efficacy and self- esteem were the best predictors in the grouping process. Conclusion: The instrument developed showed its accuracy and precision in the process of obtaining the necessary information to evaluate the factors of protection of mental health in Cuban university students.